2001
DOI: 10.1054/bjoc.2001.2174
|View full text |Cite
|
Sign up to set email alerts
|

relA over-expression reduces tumorigenicity and activates apoptosis in human cancer cells

Abstract: The mammalian nuclear factor-kappa B (NF-kB) family comprises 5 members (p50, p52, relA/p65, c-rel and relB) which form a different array of homo-and hetero-dimers and are regulated by a group of citoplasmic inhibitors (IBs) (Krappmann et al, 1999). In unstimulated cells, it is retained in an inactive cytoplasmatic form by one of several IB molecules. Activation of NF-kB complexes by a variety of stimuli results in the phosphorylation and rapid degradation of IBs through the ubiquitin-proteasome pathway (Thano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 41 publications
4
39
0
Order By: Relevance
“…Third, transgenic mice that express a constitutive IkBa inhibitor, which would inhibit all Rel/NF-kB activity, in skin cells develop squamous cell carcinomas (van Hogerlinden et al, 1999). Fourth, overexpression of rela has recently been shown to decrease the tumorigenicity of a breast cancer cell line (Ricci et al, 2001). The inability of RelA mutants that are selectively Figure 4 Re-expression of RelA proteins (wild-type or C216S or S276A mutants) in rela7/7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Third, transgenic mice that express a constitutive IkBa inhibitor, which would inhibit all Rel/NF-kB activity, in skin cells develop squamous cell carcinomas (van Hogerlinden et al, 1999). Fourth, overexpression of rela has recently been shown to decrease the tumorigenicity of a breast cancer cell line (Ricci et al, 2001). The inability of RelA mutants that are selectively Figure 4 Re-expression of RelA proteins (wild-type or C216S or S276A mutants) in rela7/7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kanno et al [33] demonstrated that the overexpression of NFkB is a pivotal event for apoptosis in HL60 cells induced by the flavonoid naringenin. It has been shown that the transcription factor NFkB participated in cell growth, differentiation, inflammatory responses induced by different signals related to the regulation of apoptosis and neoplastic transformation [34,35]. The pro-and antiapoptotic regulatory functions of NFkB have been shown to depend on the cell type, the differentiation state of the cell, and the nature of the apoptotic stimulus [35].…”
Section: Effect Of Fisetin On Mapks Phosphorylation and Nfkb Expressimentioning
confidence: 99%
“…8 Stimulation of the NF-kB pathway is essential for p53-mediated cell death 9 and expression of RelA alone promotes apoptosis in some cell types. 10 However, despite evidence linking NF-kB to the promotion of apoptosis, the mechanisms underlying this effect have yet to be fully resolved.…”
mentioning
confidence: 99%